Wellness and Discrimination in Counselor Education - Brett K. Gleason; Madeline Clark; Lena Salpietro; Rachel Jacoby (Teaching and Supervision in Counseling, 2024)
Wellness and diversity are cornerstones of professional counseling; however, both have received little attention in terms of counselor educators and their students. The results of a quantitative study (N = 301) explored the relationship between wellness and experiences of discrimination for counselor educators, doctoral students, and master’s counseling students. Researchers utilized the Five Factor Wellness Inventory, Everyday Discrimination Scale, and a demographic questionnaire to conduct both a hierarchical linear regression and a factorial ANOVA to answer research questions. Results of the study indicated that both perceived discrimination and identity factors significantly impact wellness levels for individuals within counselor education. Implications for the field such as modeling, mindfulness, and individualized wellness for both students and counselor educators are discussed.
Keywords: discrimination; wellness; counselor education